Modified Strichartz estimates with an application to the critical nonlinear Schrödinger equation. (January 2016) - Nakamura, Makoto; Wada, Takeshi
Abstract: The Cauchy problem for the critical nonlinear Schrödinger equation is considered in the Sobolev space of fractional order. Some modified Strichartz estimates are constructed and applied to the problem to obtain small global solutions with less regularity assumption for the nonlinear term.